Studi Fenomenologi: Pengalaman Remaja dalam Menggunakan Narkoba - Ketut Suryani; Bangun Dwi Hardika; Maria Tarisia Rini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to explore and explore in-depth the experiences of adolescents in using drugs. This research method uses qualitative research methods with a phenomenological approach. The results of the study obtained twelve themes, namely: 1) The age of adolescents using drugs, 2) The initial causes of adolescents using drugs, 3) The frequency of drug use in adolescents, 4) The types of drugs used by adolescents, 5) How adolescents get drugs, 6) Adolescent's efforts to stop using drugs, 7) Adolescent's feelings after using drugs, 8) The expectations of adolescents who use drugs, 9) The impact of adolescents using drugs, 10) The effects of adolescents if they do not use drugs, 11) Youth perceptions of drugs, 12) Adolescent response when using drugs. In conclusion, the impact of using drugs on adolescents was that some adolescents said they were thin, lost their parents, and quit school. Keywords: Colaizzi, Phenomenology, Drugs, Teenagers